The Effect of Using Biopore on Flood Reduction in District of Besuki, Tulungagung Regency - Khusna, Nur Isroatul; Amin, Saiful; Sekarrini, Cipta Estri (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
The District of Besuki is one of the regions in Tulungagung Regency which has karst morphology. The high quantity of rainfall and unpredictable weather in the karst area can increase the risk of natural disasters such as floods and landslides. The technology of making biopore infiltration holes can be used as one of the solutions in flood disaster mitigation efforts. These infiltration holes generally used in dense areas of settlements or regions that have minimal water catchment areas. This study aims to determine the use of biopore to prevent flood in Gambiran, Besole Village, district of Besuki, Tulungagung Regency. This type of research is an experiment. The measure water absorption was utilizing a variety of tools such as double-ring infiltrometer, stopwatch, special ruler measuring the water speed. The results showed that the use of biopore is effective in reducing the impact of flooding in karst topographic areas, especially in Gambiran Hamlet, Besole Village, Besuki district, Tulungagung Regency. This was proven by experiments conducted by making comparisons between treated soils with biopore infiltration holes and soils without any treatment. During one month, with four times the treatment of water absorption can increase more than doubled. If the point without treatment is only able to absorb water as deep as 23 cm / 30 minutes or an average of 0.7 cm/minute, then the treatment point can absorb water as deep as 57cm / 30 minutes or with an average value of 1.9 / minute. With the increasing absorption of groundwater, the use of biopore infiltration holes can reduce the impact of flooding in karst areas, especially in Gambiran Village Besole Village Besuki District Besuki Tulungagung Regency.